2022
DOI: 10.1259/bjr.20211272
|View full text |Cite
|
Sign up to set email alerts
|

Imaging CXCR4 receptors expression for staging multiple myeloma by using 68Ga-Pentixafor PET/CT: comparison with 18F-FDG PET/CT

Abstract: Objectives: 68Ga-Pentixafor PET imaging targets CXCR4 expression which is over expressed in multiple myeloma (MM). In this study, we evaluated the diagnostic utility of 68Ga-Pentixafor PET/CT for imaging CXCR4 expression in multiple myeloma and compared results with 18F-FDG PET/CT Methods: Thirty-four (21M; 13F; median age = 57.5 years) treatment naive multiple myeloma patients were recruited. All the patients underwent 18F-FDG PET/CT and 68Ga-Pentixafor PET/CT imaging. Freshly prepared 68Ga-Pentixafor (148–18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…It has been reported that overexpression of CXCR4 receptors is responsible for tumour cell proliferation, migration and invasion in many human cancer types [36]. 68 Ga-Pentixafora PET tracer for in vivo targeting of CXCR4 receptors had been validated preclinically and in different human cancers [28][29][30][31][32]37]. CXCR4 expression has been reported to be up-regulated in osteosarcoma and plays an important role in distant metastases, thus, this class of chemokines present potential targets for theranostic applications [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that overexpression of CXCR4 receptors is responsible for tumour cell proliferation, migration and invasion in many human cancer types [36]. 68 Ga-Pentixafora PET tracer for in vivo targeting of CXCR4 receptors had been validated preclinically and in different human cancers [28][29][30][31][32]37]. CXCR4 expression has been reported to be up-regulated in osteosarcoma and plays an important role in distant metastases, thus, this class of chemokines present potential targets for theranostic applications [38].…”
Section: Discussionmentioning
confidence: 99%
“…Another 68 Ga-labelled PET imaging agent, that is, 68 Ga-Pentixafor, which targets the CXCR4 chemokine receptors over-expressed in over 30 different human cancers, has been developed. 68 Ga-Pentixafor PET/CT has shown promising results in some haematological and solid malignancies overexpressing the CXCR4 receptors [28][29][30]. 68 Ga-Pentixafor PET/CT has also been reported to show the feasibility of in vivo imaging of CXCR4 expression in sarcoma and its metastatic spread [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…CXCR4 stromal cell derived 1-α factor is critical in cancer growth and metastasis. Typically, the rising activity of this factor in lymph nodes, bone, bone marrow, lung and liver has been reported to trigger the metastasis of CXCR4 expressing tumor cells [24][25]. CXCR4 receptors' over-expression thus has been recognized as an adverse prognostic factor in various malignancies including lung cancer [26-28].…”
Section: Discussionmentioning
confidence: 99%
“…Expert panel statement I: CXCR4-directed molecular imaging may be useful for marginal zone lymphoma patients CXCR4-directed Molecular Imaging CXCR4 upregulation in varying tumour entities render it as an attractive target to identify cancerous tissue [5], which can be exploited using CXCR4-directed radiotracers, including the cyclic 68 Ga-labelled CXCR4-binding pentapeptide CPCR4.2 ([ 68 Ga]Ga-PentixaFor) [6]. Relative to the most widely used PET radiotracer 2-deoxy-2-[ 18 F]fuoro-D-glucose ([ 18 F]FDG), [ 68 Ga]Ga-PentixaFor often achieved equal, sometimes superior or at least complementary diagnostic performance in nuclear oncology [7,8,9,10]. Accordingly, [ 68 Ga]Ga-PentixaFor has been extensively tested to identify sites of disease in patients with solid tumours and haematological malignancies, providing promising results for marginal zone (MZL, ▶ Fig.…”
Section: Introductionmentioning
confidence: 99%